Targeting Cannabinoid Signaling in the Immune System: “High”-ly Exciting Questions, Possibilities, and Challenges - Oláh, Attila; Szekanecz, Zoltán; Bíró, Tamás (Frontiers in Immunology, 2017)
It is well known that certain active ingredients of the plants of Cannabis genus, i.e. the “phytocannabinoids” (pCB; e.g. (-)-trans-Δ9-tetrahydrocannabinol [THC], (-)-cannabidiol [CBD], etc.) can influence a wide array of biological processes, and the human body is able to produce endogenous analogues of these substances (“endocannabinoids” [eCB] e.g. arachidonoylethanolamine [anandamide, AEA], 2-arachidonoylglycerol [2-AG], etc.). These ligands, together with multiple receptors (e.g. CB1 and CB2 cannabinoid receptors, etc.), and a complex enzyme and transporter apparatus involved in the synthesis and degradation of the ligands constitute the endocannabinoid system (ECS), a recently emerging regulator of several physiological processes. The ECS is widely expressed in the human body, including several members of the innate and adaptive immune system, where eCBs, as well as several pCBs were shown to deeply influence immune functions thereby regulating inflammation, autoimmunity, anti-tumor, as well as anti-pathogen immune responses, etc. Based on this knowledge, many in vitro and in vivo studies aimed at exploiting the putative therapeutic potential of cannabinoid signaling in inflammation-accompanied diseases (e.g. multiple sclerosis) or in organ transplantation, and to dissect the complex immunological effects of medical and “recreational” marijuana consumption. Thus, the objective of the current article is (i) to summarize the most recent findings of the field; (ii) to highlight the putative therapeutic potential of targeting cannabinoid signaling; (iii) to identify open questions and key challenges; and (iv) to suggest promising future directions for cannabinoid-based drug development.